2010
DOI: 10.1159/000320789
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic 2009 H1N1 Influenza in Patients with Hematopoietic Stem Cell Transplantation and Hematologic Malignancy: Single Center Experience

Abstract: Although valuable information on many aspects of the pandemic 2009 H1N1 influenza came to light in a relatively short period of time, the disease course among immunocompromised patients is largely unknown. In this study, we present the results of active H1N1 surveillance in 32 patients who were treated at our hematology/stem cell transplantation clinic between December 2009 and January 2010. We also report the clinical and laboratory features of patients with laboratory-proven disease and try to define the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Symptoms presented by our patients were similar to those described in non-immunosuppressed patients, [3][4][5]7,11,13,15,20 frequent complaints. Patients with HM presented with more fever than patients with solid tumors.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Symptoms presented by our patients were similar to those described in non-immunosuppressed patients, [3][4][5]7,11,13,15,20 frequent complaints. Patients with HM presented with more fever than patients with solid tumors.…”
Section: Discussionsupporting
confidence: 84%
“…Symptoms presented by our patients were similar to those described in non‐immunosuppressed patients, despite it has been suggested that immunocompromised patients might develop severe influenza without classical symptoms. Cough, fever, malaise with bone and muscle pain, rhinorrhea, and chills were frequent complaints.…”
Section: Discussionsupporting
confidence: 79%
“…Although there are concerns regarding possible neuropsychiatric reactions to highdose oseltamivir (16), a high dose has generally been found to be safe (17). Several reports noted that severely ill patients may benefit from high-dose oseltamivir therapy (18)(19)(20)(21). There were no adverse events related to high-dose oseltamivir in the present study.…”
Section: Discussionmentioning
confidence: 55%
“…Some centers report relatively mild 2009 A/H1N1 influenza disease in HSCT recipients, mainly in children , with others reporting severe pandemic A/H1N1 2009 influenza . The largest study of the pandemic A/H1N1 2009 influenza included 64 European HSCT centers reporting 286 patients, 222 after allogeneic transplantation and 64 after autologous HSCT.…”
Section: Morbidity and Mortality Due To Influenzamentioning
confidence: 99%